Different mechanisms involved in liraglutide and glucagon‐like peptide‐1 vasodilatation in rat mesenteric small arteries. (9th December 2018) - Bangshaab, Maj; Gutierrez, Alejandro; Huynh, Khiem Dinh; Knudsen, Jakob Schöllhammer; Arcanjo, Daniel Dias Rufino; Petersen, Asbjørn G; Rungby, Jørgen; Gejl, Michael; Simonsen, Ulf
Abstract : Background and Purpose: Glucagon‐like peptide‐1 (GLP‐1) is an incretin hormone that regulates insulin biosynthesis and secretion in a glucose‐dependent manner and has been reported to induce vasodilatation. Here, we examined the possible vasorelaxant effect of GLP‐1 and its underlying mechanisms. Experimental Approach: Rat mesenteric arteries (diameter ≈ 200–400 μm) and human s.c. arteries were mounted in microvascular myographs for isometric tension recordings. The effect of GLP‐1 on vascular responses was examined under normoglycaemic conditions and at high glucose concentrations. Key Results: In rat mesenteric arteries and human s.c. arteries without branches, physiological concentrations (1–100 nM) of GLP‐1(7‐36) and liraglutide failed to cause relaxation or affect contractions evoked by electrical field stimulation. In contrast to GLP‐1(7‐36), liraglutide induced relaxations antagonized by the GLP‐1 receptor antagonist, exendin‐(9‐39), in branched mesenteric arteries. In contrast to liraglutide, GLP‐1 leftward shifted the concentration relaxation curves for bradykinin in s.c. arteries from patients with peripheral arterial disease, an effect resistant to exendin‐(9‐39). Under normoglycaemic conditions, neither GLP‐1 nor liraglutide affected ACh relaxation in rat mesenteric arteries. In arteries exposed to 40 mM glucose, GLP‐1, in contrast to liraglutide, potentiated ACh‐induced relaxation by a mechanism that was not antagonized by exendin‐(9‐39). GLP‐1 decreased superoxide levels measured with dihydroethidium in rat mesenteric arteries exposed to 40 mM glucose. Conclusions and Implications: GLP‐1 receptors are involved in the liraglutide‐induced relaxation of branched arteries, under normoglycaemic conditions, while GLP‐1 inhibition of vascular superoxide levels contributes to GLP‐1 receptor‐independent potentiation of endothelium‐dependent vasodilatation in hyperglycaemia.